A chiral dumbbell shaped bis(fullerene) oligoelectrolyte - Chronakis, Nikos; Hartnagel, Uwe; Braun, Martin; Hirsch, Andreas (Chemical Communications, 2007)
The first icosacationic bis(fullerene) whose water solubility is provided by twenty peripheral ammonium groups has a rigid, almost cylindrical shape and was synthesized by connecting two fullerene cores with a chiral cyclo-bis(malonate), followed by the regioselective addition of ten amino-terminated malonates into the octahedral positions of the fullerene moieties and subsequent cleavage of the Boc-protecting groups. © The Royal Society of Chemistry.